The story of writing, from cave art to computer - Cahn, William; Chan, Rhoda (Folkestone Bailey Brothers & Swinfen, 1963)
Presents an overview of written communication by recounting the development of alphabets and numerals by various cultures and describing inventions such as paper, printing presses, and computers.
1
Keywords: Writing -- History -- Juvenile literature